Prosedur Pembiayaan Pembelian Kendaraan Bermotor Dengan Prinsip Murabahah Pada PT. Bank Pembiayaan Rakyat Syariah Al-Falah Banyuasin - Venny Jannatul Putri; Moh. Faizal (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2018)
PT. BPRS al-falah banyuasin provides financing for the purchase of motorized vehicles with a murabahah contract, where customers must follow the existing procedures, namely; financing application procedures, financing approval procedures, financing approval procedures, financing binding procedures, financing disbursement procedures, and installment financing procedures as well as guarantees repayment and release procedures. This study aims to determine the financing procedure for purchasing a motorized vehicle with a murabahah contract and the constraints faced and resolved at PT. Al-Falah Islamic people's finance bank is mostly used by using the type of data in the form of qualitative descriptive. This study also uses the interview method with questions about the financing procedure for purchasing motorized vehicles with a murabahah contract at PT. BPRS All-falah banyuasin. Constraints encountered and how to solve them. Results and discussion of financing procedures for purchasing motorized vehicles with a murabahah contract at PT. BPRS Al-Falah banyuasin shows that the financing procedure has been running well and has been implemented in accordance with the policies of the financing committee and financing procedures.